And the men backed down! while Deborah led the war (2022)
Women of all ages have been major players on world stage. In the course of history, the narrative was manipulated leading to women being marginalised in the scheme of things in the socio-economic and political realms while men take the centre stage. The fields of gender and feminist studies are fertile grounds for the discourse on obliteration of women and their positive contribution to human development. The biblical example of Deborah in the book of Judges was used in the discussion of this theme. A critical analysis of Deborah's contributions to the restoration of Israel to God and its socio-political development was undertaken deploying Judith Butler's theory of performativity. This paper foregrounds that the basis for classifying women as subservient to the male gender in all endeavours of life is unfounded. Even though malestreaming of human endeavours is somewhat intractable, recent discoveries in the fields of gender and feminist studies are exposing the facticity of female performance of acts that male supremacist cultures fail to credit to amazons from antiquity to modem days.